2021
DOI: 10.1308/rcsann.2021.0062
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism causing posterior reversible encephalopathy syndrome: a case report

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a reversible leukoencephalopathy characterised by subcortical vasogenic oedema and neurological signs. We present the case of a 64-year-old woman who presented to hospital with symptomatic primary hyperparathyroidism. Her parathyroid hormone (PTH) level on admission was elevated at 1,330ng/l (normal range15–68ng/l) and her serum calcium measured 4.83mmol/l (normal range 2.25–2.54mmol/l). Technectium-99m sestamibi scan demonstrated a focus of radiotracer up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Both hyperthyroidism and hypothyroidism are associated with adverse pregnancy outcomes, such as miscarriage, intrauterine growth retardation, preterm delivery, and pre-eclampsia [30,31]. According to literature review, Hashimoto encephalopathy and [32] hyperthyroidism have been reported to be related to [33] PRES, while the specific mechanism remains unclear. Whether eclampsia lies the link between hypothyroidism and PRES requires to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperthyroidism and hypothyroidism are associated with adverse pregnancy outcomes, such as miscarriage, intrauterine growth retardation, preterm delivery, and pre-eclampsia [30,31]. According to literature review, Hashimoto encephalopathy and [32] hyperthyroidism have been reported to be related to [33] PRES, while the specific mechanism remains unclear. Whether eclampsia lies the link between hypothyroidism and PRES requires to be further studied.…”
Section: Discussionmentioning
confidence: 99%